Ethics of psychology research: a review to ethics codes of Argentina, Brazil and Colombia (Revista de Psicología, 2019)
This proposal discusses the ethical considerations on research done in three codes: the 1090 (2006) law governing the practice of psychologists in Colombia, the Code of Ethics do Profissional do Conselho Federal Psychologist of Psychology in Brazil and the National Code of Ethic in Argentina. The analysis of the precepts on dealing with people, informed consent and information management, and animal research, to appreciate strengths and deficiencies in each country’s codes, as well as the particularities of the concept of a research psychologist’s role in nowadays society.
Keywords: Psychology; ethics; research